Case Study: Application of Slow Deep Breathing and Murottal Al-Qur'an Therapy to Reduce Chest Pain in Coronary Artery Disease (CAD) Patient - Vira Amelia; Aan Nuraeni; Ristina Mirwanti (Universitas Padjadjaran, 2022)
Acute coronary syndrome (ACS) occurs due to sudden cessation of coronary blood flow so that blood flow to the myocardium is disrupted, which causes chest pain. Pain management can be done by providing slow deep breathing and murottal Al-Qur'an intervention. This study aimed to analyze the intervention of slow deep breathing and murottal Al-Qur'an in reducing chest pain in patients with acute coronary syndrome. This type of research was a case study in patients with acute coronary syndrome by exploring the problem of nursing care with a descriptive method through a nursing care approach. The chest pain scale was measured using a numerical rating scale (NRS) instrument. The pain measurement tool for the numerical questionnaire Rating Scale uses numbers from 0 to 10 to express patients' pain levels. The results showed that on the first day, there was no decrease in pain intensity. The pain score was on a scale of 6 before and after the intervention. On the second day, there was a decrease in pain from a scale of 6 to a scale of 5. The third day of the intervention showed a decrease in pain to a scale of 3. The intervention of slow deep breathing and murottal Al-Qur'an can potentially reduce the scale of chest pain in patients with acute coronary syndrome. Future research is expected to see the effectiveness of slow deep breathing and murottal Al-Qur'an in reducing chest pain in patients with acute coronary syndrome